Shaken to the core - understanding the impact of infant trauma - Sztuba, Karolina; Rutkowski, Wojciech; Gajdzińska, Natalia; Salwa, Adam; Rzepka, Maciej; Rymaszewska, Katarzyna; Starzomska, Dominika; Puchała, Justyna; Basiura, Karolina; Rostkowska, Weronika (Quality in Sport, 2024)
Introduction: Shaken Baby Syndrome (SBS), a severe form of abusive head trauma (AHT), primarily affects infants due to their vulnerable anatomy and physiology. SBS results from violent shaking, causing the brain to collide with the skull, leading to critical injuries including brain damage and long-term disabilities. Despite its severity, SBS is often misperceived as non-harmful, leading to delays in diagnosis and intervention. Materials and Methods: The study involves a comprehensive review of SBS and AHT related literature from the last 10 years available in English, focusing on the mechanisms, epidemiology, clinical presentation, and diagnostic challenges associated with the syndrome. Aim of the Study: The primary aim is to elucidate the diagnostic difficulties and underrecognized nature of SBS. The study seeks to raise awareness among healthcare providers and caregivers about the critical need for early detection and intervention. It also aims to emphasize the importance of educational programs to prevent SBS and improve outcomes for affected children. Conclusion: SBS is a severe and frequently underrecognized form of child abuse with potentially devastating consequences. Effective prevention and intervention hinge on improved awareness and education. Raising consciousness among healthcare providers and the general public, along with implementing robust educational initiatives, is crucial to reduce the incidence and impact of SBS. Early diagnosis and intervention, supported by targeted education, are essential to protecting vulnerable children and mitigating long-term harm.